Comprehensive review on the adsorption of pharmaceutical products from wastewater by clay materials - Oumaima Fraiha; Nouhaila Hadoudi; Najlae Zaki; Amin Salhi; Hassan Amhamdi; El Houssien Akichouh; Fouad Mourabit; M'hamed Ahari (Desalination and Water Treatment)
The over-consumption, inappropriate use and dumping of pharmaceutical products have had adverse effects on ecosystems. The presence of pharmaceutical contaminants in surface waters and drinking water is of worldwide concern, due to their ability to produce physiological effects even at low concentrations in humans and animals. These compounds find their way into the environment mainly through human and animal waste, and their mode of action and persistence are among today's major environmental challenges. Traditional wastewater treatment methods used to address these challenges have many significant drawbacks. In response, adsorption is gaining in popularity within the scientific community due to its high performance, low cost, ease of handling and diversity of adsorbents. This review highlights the application of a variety of adsorbents for efficient removal of pharmaceuticals from different media. Among these adsorbents, clays have attracted particular attention thanks to their economic potential and efficiency. Their use represents a promising solution to this environmental problem.